Pengaruh Motivasi dan Lingkungan Kerja Terhadap Produktivitas Kerja pada Karyawan Dealer Motor Listrik Jogja (BANZ ELECTRIC MOTORCYCLE) - Melinda Kartikaningrum; Kristiana Sri Utami (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to determine the influence of motivation and work environment on work productivity both partially and simultaneously. The population of this research is employees at the Jogja Electric Motorcycle Dealer (BANZ ELECTRIC MOTORCYCLE), totaling 20 employees. and the sampling technique used is saturated sampling. This type of research includes quantitative research. Data collection was carried out using primary data. The data collection technique in this research is a questionnaire. The measurement scale uses a Likert scale. Data analysis uses multiple regression tests with the SPSS 24 program. Based on the results of data analysis, it is known that the Motivation variable has no influence and is not significant on Work Productivity, the Work Environment variable has a significant influence on Work Productivity, and the Motivation and Work Environment variables simultaneously have an influence positive and significant on Work Productivity. As a consideration, companies should pay more attention to the motivation provided, and continue to pay attention to the work environment so that employee work productivity results can increase.